Evaluation of effects of Cuminum cyminum and Probiotic on Staphylococcus aureus in Feta Cheese - E Sadeghi; A Akhondzadeh Basti; A Misaghi; T Zahraii Salehi; S Bohlouli Osgoii (Institue of Medicinal Plants, ACECR, 2010)
Background: Cuminum cyminum is one of the Iranian traditional spices and it has antimicrobial effect on the pathogenic bacteria which are agents for some current food born intoxications. Probiotics have known as health and immune system booster. Objective: Evaluation of antimicrobial effect of mentioned plant essential oil in combination with lactobacillus acidophilus on Staphylococcus aureus in Feta cheese. Methods: The essential oil of this plant was obtained by hydrodistillation and analyzed by GC/MS. Effects of different concentrations of this essential oil and lactobacillus acidophilus on Staphylococcus aureus were determined by evaluation of the microorganism growth on the selective media in laboratory, and these were took place in Feta cheese. Results: Results indicated that 0.03 and 0.015 percent of this essential oil have had the highest inhibitory effect on the growth of Staphylococcus aureus and when the mentioned concentrations of the essential oil were used in combination with lactobacillus acidophilus, the counts of the pathogen were decreased significantly bellow its toxic dose in this kind of food product. Results indicated that each one of mentioned concentrations of the essential oil and lactobacillus acidophilus, was significant. The synergistic impact between mentioned concentrations of the essential oil and lactobacillus acidophilus was significant. Conclusion: The antimicrobial effect of Cuminum cyminum in 0.03 percent was higher than its lesser concentrations and with concern to the control group, the synergistic effect between the probiotic and the essential oil is necessary to achieve this inhibitory effect.